DOES TROTSKYSM HAVE ROCK? CONTROVERSIES AND TENSIONS BETWEEN LEFTIST MILITANCY AND COUNTERCULTURAL ARGENTINE ROCK (1974-1980) - Mangiantini, Martín (Revista de Historia Social y de las Mentalidades, 2021)
This paper will analyze two cultural publications edited by Argentine Trotskyism, La Chispa and Propuesta, thought to approach the youth. The first one emerged as a youth organ of the Socialist Workers’ Party in political radicalization around 1974 and 1975. The other one, a subsidiary of the same organization but without visible political reference, circulated during the years of the last civil-military dictatorship. The work focuses on dialogue and tensions between two areas: left-wing militancy and rock as a genre and countercultural expression.
Keywords: Trotskyism; Rock; Militancies; Cultural Publication